2007
DOI: 10.1007/s00253-007-0841-z
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic biodegradation of pentachlorophenol in a fixed-film reactor inoculated with polluted sediment from Santos–São Vicente Estuary, Brazil

Abstract: This paper discusses the results of pentachlorophenol (PCP) anaerobic biodegradation in a horizontal-flow anaerobic immobilized biomass (HAIB) reactor operated under methanogenic and halophylic conditions. The system was inoculated with autochthonous microorganisms taken from a site in the Santos-São Vicente Estuary (state of São Paulo, Brazil) severely contaminated with PCP, phenolic compounds, polychlorinated biphenyls, polycyclic aromatic hydrocarbons, and heavy metals. The inoculum was previously enriched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
1
15
0
4
Order By: Relevance
“…water polluted containing phenol (Bolãnos et al 2001), formaldehyde (Oliveira et al 2004), pentachlorophenol (Saia et al 2007) and BTEX (Cattony et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…water polluted containing phenol (Bolãnos et al 2001), formaldehyde (Oliveira et al 2004), pentachlorophenol (Saia et al 2007) and BTEX (Cattony et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…2014). Essentially, in the anaerobic environment, PCP degradation is a microbial dechlorinated respiration process, during which the chlorinated compounds serve as terminal electron acceptors (Saia et al 2007;Payne et al 2011). In our previous study, Chen et al (2012) revealed that the dechlorinated products of degradation of PCP are 2,3,5,6-tetrachlorophenol (TeCP) and 2,3,5-trichlorophenol (TCP), and Tong et al (2014) also found the similar intermediates in dechlorination of PCP.…”
Section: Introductionmentioning
confidence: 99%
“…Ye e Shen (2004) De acordo com os resultados da partida do RAHLF 1, a estratégia adotada para a partida do RAHLF 2 foi o aumento gradual de concentração do PCP. Esta estratégia tem sido utilizada por outros autores (WU et al, 1993;JUTEAU et al, 1995;DAMIANOVIC, 1997;TARTAKOVISKY et al, 2001;MONTENEGRO et al, 2001;LANTHIER et al, 2005;SAIA et al, 2007) no estudo de degradação de PCP, independentemente do típo de inóculo e do reator utilizado e parece ser necessária para adaptação da comunidade microbiana, mais especificamente dos grupos metanogênicos sensíveis a compostos xenobióticos (LANTHIER et al, 2005). Wu et al (1993) operaram um reator UASB por um período inicial de 5 dias sem a adição de PCP.…”
Section: Estratégias De Partidaunclassified
“…A estratégia adotada permitiu que o PCP fosse desalogenado em compostos menos clorados e que elevadas taxas de remoção de matéria orgânica total fosse obtida. Saia et al, (2007) também estudou a degradação do PCP em RAHLF e começou a operação com 5,0 …”
Section: Estratégias De Partidaunclassified
See 1 more Smart Citation